Fedor Yefimovich Vasilyuk - none (Клиническая и специальная психология, 2017)
September 17, 2017 psychology suffered an irreparable loss – Fyodor Vasilyk passed away. Fedor Vasilyk was doctor of psychological sciences, professor, head of chair of individual and group psychotherapy of Moscow State University of Psychology and Education. He was founder of the department of psychological counseling and permanent dean of that department for 15 years. Fedor Vasilyk was president of Association of psychology of experiencing, chief researcher of the laboratory of scientific basics of psychology of counseling and psychotherapy of the Psychological Institute of RAE. The psychological community mourns the untimely death of Fedor Vasilyk and expresses deep condolences to his family and friends.